Factors Associated With the Presence of Tuberculous Empyema in Children With Pleural Tuberculosis - Wu, Yan-Hua; Wang, Jun-Li; Wang, Mao-Shui (Frontiers in Pediatrics, 2021)
Background Until now, the factor of tuberculous empyema (TE) in children with pleural tuberculosis (TB) remains unclear. Therefore, a retrospective study was conducted to assess the factors associated with the presence of TE in children. Methods Between January 2006 and December 2019, consecutive children patients (≤ 15 years old) with suspected pleural TB were selected for further analysis. Empyema was defined as grossly purulent pleural fluid. The demographic, clinical, laboratory, and radiographic features were collected from the electrical medical records retrospectively. Univariate and multivariate logistic regressions were used to explore the factors associated with the presence of TE in children with pleural TB. Results A total of 154 children with pleural TB (definite, 123 cases; possible, 31 cases) were included in our study and then were classified as TE (n=27) and Non-TE (n=127) groups. Multivariate analysis revealed that surgical treatment (age- and sex-adjusted OR=92.0, 95% CI: 11.7, 721.3), cavity (age- and sex-adjusted OR=39.2, 95% CI: 3.2, 476.3), pleural LDH (>941 U/L, age- and sex-adjusted OR=14.8, 95% CI: 2.4, 90.4), and temperature (> 37.2 ℃, age- and sex-adjusted OR=0.08, 95% CI: 0.01, 0.53) were associated with the presence of TE in children with pleural TB. Conclusion Early detection of the presence of TE in children remains a challenge and several characteristics, such as surgical treatment, lung cavitation, high pleural LDH level, and low temperature were identified as factors of the presence of TE in children with pleural TB. These findings may improve the management of Childhood TE.